Speed demands of women's rugby sevens match play - Misseldine, N. D.; Blagrove, R. C.; Goodwin, J. E. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to quantify the running speed demands of elite female rugby sevens match play, both absolute and relative to maximal ability, and determine the importance of maximal velocity running to performance. Individual maximal running velocity (Vmax) was established for 12 professional female rugby sevens athletes before the collection of global positioning system data during all 6 games of an international tournament. The subjective importance of each maximal velocity running effort was established using visual analogue scale ratings of video clips by coaches. Differences in velocity demands between backs and forwards were analyzed using a one-way multivariate analysis of variance, and differences in "sprint" distance using the typical-standard and female-adjusted sprint thresholds were compared using a paired-samples t-test. The mean peak velocity reached per game by all players was 90.6 ± 7.9% Vmax. Players covered 1,556 ± 233 m per game, with "sprinting" representing 6 ± 4% of this total distance using the typical-standard "sprint" threshold (5.6 m/s), but a significantly (p < 0.001) greater 12 ± 4% using the female-adjusted threshold (4.7 m/s). Despite similar total distances, backs reached significantly (p < 0.05) greater peak running velocity and covered more distance at sprint, >75% Vmax and >90% Vmax speeds when compared to forwards. More than half of the running efforts peaking at =90% Vmax were considered very influential to game outcomes. These findings suggest that maximal velocity running is important to female rugby sevens performance, and that high-speed demands are different for backs and forwards. Furthermore, the typical-standard sprint thresholds significantly underestimate the true running demands of female rugby sevens.